La auto-grafolatría de la lengua griega: el valor de la escritura en la obra de Gregorio Prieto - Carrasco Castro, Mª Isabel (Escritura e Imagen, 2007)
The painter Gregorio Prieto approaches writing from two essential points of view: the incorporation of words in his paintings, most notably the words written in Greek characters, and the writing of his own name. The fact that Gregorio includes Greek words in his paintings or that he signs in Greek, even though he did not know this language, allows us to analyze the use of writing and specifically the Greek alphabet from two different perspectives: the inner concept of words: “the signifien” Greece and Gregorio, and the value of writing “having meaning”. This last sense leads us to believe that Gregorio recuperated the primary use of writing and that he returned to it its aesthetic aspect. The Greek alphabet, although phonetic, was the essence of Greek-ness for the artist, (here we can introduce the term grapholatry) and through it, he would transform his signature into an emblem and ex-scribe and to in-scribe himself as a /in Greek.